2022
DOI: 10.3390/ph15020181
|View full text |Cite
|
Sign up to set email alerts
|

Human Enterovirus B: Selective Inhibition by Quinoxaline Derivatives and Bioinformatic RNA-Motif Identification as New Targets

Abstract: The Enterovirus genus includes many viruses that are pathogenic in humans, including Coxsackie viruses and rhinoviruses, as well as the emerging enteroviruses D68 and A71. Currently, effective antiviral agents are not available for the treatment or prevention of enterovirus infections, which remain an important threat to public health. We recently identified a series of quinoxaline derivatives that were provento be potent inhibitors of coxsackievirus B5, the most common and a very important human pathogen belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This CV-selective activity could be partially explained by differences in the VP-1 protein sequences. Moreover, an RNA-binding motif analysis through an RNA-Binding Protein DataBase (RBPDB) aimed at revealing new targets in CVs, revealed that only CV-3 and CV-4 share the binding motif for SRSF13, a serine-arginine rich splicing factor involved in splicing events which might alter viral replication and be a potential innovative target for these compounds [ 18 ].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…This CV-selective activity could be partially explained by differences in the VP-1 protein sequences. Moreover, an RNA-binding motif analysis through an RNA-Binding Protein DataBase (RBPDB) aimed at revealing new targets in CVs, revealed that only CV-3 and CV-4 share the binding motif for SRSF13, a serine-arginine rich splicing factor involved in splicing events which might alter viral replication and be a potential innovative target for these compounds [ 18 ].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…Most of the FDA-approved drugs possess the N -heterocycle skeleton [ 28 ], which can be differently functionalized to obtain different compounds endowed with biological properties and, therefore, various pharmacological applications [ 29 ]. A wide number of nitrogen-containing heterocyclic derivatives were recognized to exhibit a broad range of pharmacological effects [ 30 , 31 , 32 , 33 , 34 ] and were widely reported in the literature to show intriguing biological activities for these types of compounds [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%